1990
DOI: 10.1161/01.cir.82.3.781
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of reocclusion after successful reperfusion therapy in acute myocardial infarction. TAMI Study Group.

Abstract: fractions compared with patients with sustained patency at follow-up. However, patients with reocclusion at follow-up had worse infarct-zone function at -2.7 (value, -3.2/-1.8) versus -2.4 (SD/chord) (value, -3.11-1.3) (p=0.016). The recovery of both global and infarct-zone function was impaired by reocclusion of the infarct-related artery compared with maintained patency; median A ejection fraction was -2 compared with 1 (p=0.006) and median A infarct-zone wall motion was -0.10 compared with 0.34 SD/chord (p=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
96
0
2

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 400 publications
(104 citation statements)
references
References 48 publications
6
96
0
2
Order By: Relevance
“…The reduced risk was observed consistently across many different subgroups and occurred independent of antithrombotic regimen and culprit stenosis severity, a known strong predictor of reocclusion in this setting [27][28][29]. The majority of reocclusions have been shown to occur without clinical reinfarction [12][13][14]. In our study reocclusion occurred without clinical reinfarction in almost 80% of cases, while 46% of patients with reocclusion did not experience recurrent ischemic events.…”
Section: Smoking and Reocclusionsupporting
confidence: 60%
See 3 more Smart Citations
“…The reduced risk was observed consistently across many different subgroups and occurred independent of antithrombotic regimen and culprit stenosis severity, a known strong predictor of reocclusion in this setting [27][28][29]. The majority of reocclusions have been shown to occur without clinical reinfarction [12][13][14]. In our study reocclusion occurred without clinical reinfarction in almost 80% of cases, while 46% of patients with reocclusion did not experience recurrent ischemic events.…”
Section: Smoking and Reocclusionsupporting
confidence: 60%
“…Given the strong relationship between reocclusion and outcome after successful fibrinolysis [12][13][14], previous studies addressed the risk of reocclusion in smokers in search for potential mechanisms explaining their favorable outcome. Results of these studies have been conflicting.…”
Section: Smoking and Reocclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the range of ejection fractions <50%, an end-systolic volume of > 100 mL, measured at 1 to 2 months after infarction, is an even stronger predictor of mortality.2 Treatment of myocardial infarction should thus be aimed at limitation of infarct size and preservation of end-systolic volume. Thrombolysis has been shown to improve survival after myocardial infarction3 and also improves left ventricular volume.4 Successful thrombolysis, however, is associated with a risk for reocclusion that averages 10% to 20% before hospital discharge5,6 and was recently reported to occur in almost 30% after 3 months.7 '8 Reocclusion occurs without symptoms in about half of the patients5 but is nevertheless associated with higher mortality rates, impaired recovery of left ventricular function, and a more complicated hospital course. 5 To date, no studies have been reported in which the impact of reocclusion observed after 3 months has been related to changes in global and regional ventricular function and to changes of left ventricular volumes during that period in a group of patients that did not sustain recurrent infarction after thrombolysis. For the study of ventricular function, a time window of 3 months is of interest because by then vital myocardium in patients with sustained reperfusion is likely to have completely recovered from stunning.…”
mentioning
confidence: 99%